Fisioterapi Dada dan Batuk Efektif sebagai Penatalaksanaan Ketidakefektifan Bersihan Jalan Nafas pada Pasien TB Paru di RSUD Kota Kendari - Rusna Tahir; Dhea Sry Ayu Imalia; Sitti Muhsinah (Health Information : Jurnal Penelitian, 2019)
Pulmonary tuberculosis is an infection disease with the highest prevalence in the world and being the third largest in Indonesia with 1.02 million cases. The core problem of pulmonary tuberculosis patient is ineffective airway clearance characterized by dyspnea, ronchi, excessive sputum, ineffective cough. Nursing intervention to manage the problem is chest physiotherapy and effective coughing. This study aims to obtain an overview of the application of chest physiotherapy and effective coughing as ineffective airway clearance management on pulmonary tuberculosis patient. Method: Method used descriptive case study with structured interview, studies document and observations. Participants in this study is pulmonary tuberculosis patient which is given three days and twice a day session of chest physiotherapy and effective coughing. Patency of the airway is improved after chest physiotherapy and effective coughing which characterized by normal respiratory frequencies, normal respiratory rhythms, no ronchi and able to remove sputum from airway. Chest physiotherapy and effective coughing is applicable as ineffective airway clearance management on pulmonary tuberculosis patient.